Advice to the European Commission as Regards Type and Criteria for Comprehensive Studies to Be Requested From Manufacturers: The Opinion of the Scientific Committee on Health, Environmental, and Emerging Risks (SCHEER). Issue 5 (6th March 2019) - Talhout, Reinskje; Duarte-Davidson, Raquel; Hoet, Peter; Nair, Urmila; Rydzynski, Konrad; Vermeire, Theo; Zacharov, Sergej; Testai, Emanuela
Abstract: : The European Commission has established a priority list of 15 additives contained in cigarettes and roll-your-own tobacco subject to enhanced reporting obligations. The European Union (EU) Tobacco Products Directive (TPD) prescribes that Member States shall require manufacturers and importers of tobacco products to carry out comprehensive studies on these additives to assess their contribution to any of the properties listed in Article 6 of the TPD: toxicity or addictiveness, characterizing flavor, inhalation facilitation, nicotine uptake, and carcinogenic, mutagenic, or toxic for reproduction. The Scientific Committee on Health, Environmental, and Emerging Risks (SCHEER) has provided guidance on the type and criteria for comprehensive studies, and on the most suitable methodologies to test these 15 tobacco additives as well as additives on future updated lists. The SCHEER proposes a stepwise strategy as the most pragmatic and efficient way to assess the effects of tobacco additives. In addition to proposing specific steps and tests to be considered by industry, some general criteria were also identified such as no comparative testing (testing cigarettes with and without the additive) and no animal studies. As tobacco additives have no benefits for health, but rather may promote use of and addiction to an extremely toxic product, a risk–benefit analysis is not the appropriate paradigm for assessing the additive. When comprehensive studies confirm that additives have any of the properties listed in Article 6 of the TPD, regulatory actions should be considered. If uncertainties cannot be solved by comprehensive studies, the SCHEER recommends that the assessors consider the worst-case evaluation. Implications: In this article, the SCHEER proposes a stepwise strategy to assess (1) the toxic and addictive effects, (2) the characterizing flavor, and (3) facilitating inhalation properties of tobacco additives. The proposed steps and tests provide guidance to (1) Member State on which comprehensive studies should be requested and (2) tobacco industry on which strategy of testing should be applied to address the request and to prepare reports to be sent to the relevant authorities for the evaluation of tobacco additives "safety" to comply with the Tobacco Products Directive 2014/40/EU.